Sox14 is required for transcriptional and developmental responses to 20-hydroxyecdysone at the onset of drosophila metamorphosis. - Ritter, A.R.; Beckstead, R.B. (Developmental Dynamics, 2010)
The steroid hormone 20-hydroxyecdysone (20E), by means of a heterodimer consisting of two nuclear receptors, the Ecdysone receptor (EcR) and Ultraspiracle (Usp), triggers the major developmental transitions in the Drosophila life cycle through the regulation of genetic hierarchies. We have previously demonstrated that the Sox14 transcription factor is a primary response gene to 20E/EcR/Usp complex. In this study, we show that mutations in sox14 result in prepupal and pupal lethality with animals displaying a multitude of defects in 20E developmentally regulated pathways. In addition, through Northern blot and microarray analyses of sox14 mutant animals, we demonstrate that Sox14 is required for the proper expression of 20E- and non-20E-regulated genes at the onset of metamorphosis. We also show that the Sox14-regulated gene set correlates well with Sox14 expression in a variety of larval and adult tissues. Thus, Sox14 is a critical transcription factor required for 20E signaling at the onset of metamorphosis.